SOLVING OPTIMIZATION PROBLEMS IN A WAREHOUSE WITH MATLAB CODE - Angelevska, Beti; Jakimovska, Kristina; Vasileva, Anita; Zelić, Atila; Ilanković, Nikola; Živanić, Dragan (Horizons - International Scientific Journal, 2020)
Optimization plays an important role in reducing costs, eliminating redundant activities and saving time. Thus, the way to retrieve solutions for optimization, highly depend on the theory, mathematical methods, but first, on imagination and information about the problem. The main goal of this paper is focuses on optimizing each movement, space and extra costs in warehouse through simply concepts of solving the problems.